Design and properties 1–3 multi-element piezoelectric composite with low crosstalk effects. Issue 17 (1st December 2017) - Geng, Bo; Xu, Dongyu; Yi, Shanling; Gao, Guangpeng; Xu, Hongchao; Cheng, Xin
Abstract: Piezoelectric composites are gaining increasingly importance in ultrasonic fields due to their superior properties. Here novel 1–3 multi-element piezoelectric composites were developed by using piezoelectric ceramic as functional phase, epoxy resin as matrix phase, and silica gel and polyurethane as decoupling materials. The effects of decoupling materials and composite thickness on dielectric, piezoelectric and electromechanical coupling properties of the composites were investigated. The coupling response among various elements of the composites was discussed by setting up an ultrasonic testing platform. The results show that the multi-element piezoelectric composites have larger piezoelectric voltage factor than piezoelectric ceramic, however, less relative permittivity and piezoelectric strain factor. With decreasing the composite thickness, the thickness resonant peaks of the piezoelectric composite shift toward high frequency direction, and no obvious high-order and coupling resonant peaks appear. The multi-element piezoelectric composites have larger thickness electromechanical coupling coefficient k t and less mechanical quality factor Q m than piezoelectric ceramic. When composite thickness is 5 mm, the epoxy/silica piezoelectric composite has a maximum k t value of 70.41%, and a minimum Q m value of 11.29. The coupling response testing results show that epoxy/silica piezoelectric composite shows less crosstalk effect than epoxy/epoxy and epoxy/polyurethane piezoelectric composites.